Color-coded intravital imaging demonstrates a transforming growth factor-β (TGF-β) antagonist selectively targets stromal cells in a human pancreatic-cancer orthotopic mouse model. Issue 10 (19th May 2017) - Murakami, Takashi; Hiroshima, Yukihiko; Miyake, Kentaro; Hwang, Ho Kyoung; Kiyuna, Tasuku; DeLong, Jonathan C.; Lwin, Thinzar M.; Matsuyama, Ryusei; Mori, Ryutaro; Kumamoto, Takafumi; Chishima, Takashi; Tanaka, Kuniya; et al.
ABSTRACT: Pancreatic cancer is a recalcitrant malignancy, partly due to desmoplastic stroma which stimulates tumor growth, invasion, and metastasis, and inhibits chemotherapeutic drug delivery. Transforming growth factor-β (TGF-β) has an important role in the formation of stromal desmoplasia. The present study describes the ability of color-coded intravital imaging to demonstrate the efficacy of a TGF-β inhibitor to target stroma in an orthotopic mouse model of pancreatic cancer. The BxPC-3 human pancreatic adenocarcinoma cell line expressing green fluorescent protein (GFP), which also has a high TGF-β expression level, was used in an orthotopic model in transgenic nude mice ubiquitously expressing red fluorescent protein (RFP). Fourteen mice were randomized into a control group (n = 7, vehicle, i.p., weekly, for 3 weeks) and a treated group (n = 7, SB431542 [TGF-β receptor type I inhibitor] 0.3 mg, i.p., weekly, for 3 weeks). Stromal cells expressing RFP and cancer cells expressing GFP were observed weekly for 3 weeks by real-time color-coded intravital imaging. The RFP fluorescence area from the stromal cells, relative to the GFP fluorescence area of the cancer cells, was significantly decreased in the TGF-β-inhibitor-treatment group compared to the control group. The present study demonstrated color-coded imaging in an orthotopic pancreatic-cancer cell-line mouse model can readily detect the selective anti-stromal-cell targeting of a TGF-β inhibitor.